An Empirical Study on Innovation Excellence Framework in Malaysian Higher Education Institutions Based on Partial Least Squares Structural Equation Model - Nur Balqishanis, Zainal Abidin; M. R., Abdul Hamid (UTM Press, 2016)
The purpose of this study is to develop the Innovation Excellence Framework in Malaysian Higher Education Institutions (HEIs). The Structural Equation Modelling (SEM) was used to analyze the structural relationships of latent constructs namely, Objectives & Strategy, Change Management, Best Practices, Resource Management and Innovation. A total of nine hypotheses have been put forward to test the relationships amongst these constructs of innovation excellence. Partial least squares structural equation modelling technique was used for empirically assessing the model. The data was collected from a survey that yielded 467 usable questionnaires through cluster and stratified sampling technique on the specified universities. The findings revealed that all the hypothesized relationships are significant at t-value > 1.96, two-tailed test by using 5000 bootstrap samples except for the relationship of Objectives and Strategy towards Innovation which resulted a non-significant relationship.